The Influence Of Profitability, Solvency And Asset Management On The Rate Of Return On Stock Investment - Meliyanti Sari Hardini; Nurhastuty Kesumo Wardhani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research examines the influence of profitability, solvency and asset management on the rate of return on stock investment. This research is based on agency theory and signal theory, which shows how a company's financial performance can influence investment decisions. The analysis was carried out using secondary data from the financial reports of companies listed on the Indonesia Stock Exchange (BEI) in 2022 and 2023, with a sample of companies included in the IDX80 index. The research method used is associative quantitative, which aims to examine the relationship between independent variables (profitability, solvency and asset management) and the dependent variable (rate of return on stock investment). The analysis results show that profitability has a negative influence on the rate of return on stock investment, while solvency and asset management have a positive influence. Descriptive statistical tests, classical assumption tests, and multiple linear regression were used to analyze the data. Profitability is measured using Return on Equity (ROE), solvency is measured by Debt to Equity Ratio (DER), and asset management is measured by Total Asset Turnover. The conclusion of this research emphasizes the importance of good financial performance in increasing stock returns and reducing risks for investors. These findings are relevant for investors and managers in making investment decisions and company management.